Partial Results Regarding the Genetic Analysis of Nonius Horse from Izvin Studfarm: Reproductive Isolation and Age Structure - Marius Maftei; Răzvan Popa; Dana Popa; Gheorghe Mărginean; Livia Vidu; Iulian Vlad; Mariana Gîrlea; Traian Lăpuște (Scientific Papers Animal Science and Biotechnologies, 2023)
This study is a part of an ample research concerning the genetic analysis (history) of Nonius horses from Izvin studfarm. The genetic analysis studies are a part of Animal Genetic Resources Management because just start of them we elaborate the strategies for inbreeding management. This study has as purpose to present two important aspects of genetic analysis: reproductive isolation level and age structure.This parameters has a capital importance in animal breeding because there has a directly influence in animal population evolution. The reproductive isolation situation was quantified using the relation elaborated by S. Wright in 1921. The age structure situation is based on the age distribution histogram.  The analysis showed that the Nonius horse from Izvin stud is a reproductively isolated population and have its own evolutionary path. Age structure is not balanced with negative repercurssions on generation interval.